Conglomerate Entrenchment under Optimal Financial Contracting - Faure-Grimaud, Antoine; Inderst, Roman (American Economic Review, 2005)
We provide a formal analysis of the notion that conglomerates are more ‘entrenched’ as they have ‘deeper pockets’. Using the financial contracting model of Bolton and Scharfstein (1990), we can isolate two effects that confirm this conjecture: the pooling of cash flows, which allows to smooth out repayments, and the ability to obtain better credit terms. For less profitable business segments, the internal capital market operated in a conglomerate may, however, work in the opposite direction, increasing the sensitivity of operations to own cash flows and increasing the likelihood of exit.